A new approach for coupling the short- and long-term planning models to design a pathway to carbon neutrality in a coal-based power system. (15th January 2022) - Wyrwa, Artur; Suwała, Wojciech; Pluta, Marcin; Raczyński, Maciej; Zyśk, Janusz; Tokarski, Stanisław
Abstract: Transformation towards climate-neutral energy systems is becoming a challenge worldwide. Most often, strategic planning for the mid- and long-term is tackled with the use of generation expansion optimization models, which have limited capabilities to track in detail power system operation. On the other hand, the unit commitment and economic dispatch models consider many technical constraints but are usually used for short-term planning. The methodological approach presented in this paper aims to improve the planning capabilities by the combination of generation expansion and short-term planning models into one modelling system. Two models were coupled, namely TIMES-PL and MEDUSA, to design a pathway to carbon neutrality in the Polish power system. Three energy scenarios elaborated in this work show that a 95 % reduction in carbon dioxide emissions from the public electricity and district heat production sectors is possible by 2050. The proposed approach improved the robustness of elaborated energy scenarios as in their first versions two of them turned out to be technically infeasible. Detail simulations of the system operation showed that load balancing is possible once 15–20 GW of electrical capacity is installed in dispatchable power generation technologies by 2050 in addition to energy storage and combined heat and power plants. Highlights: Generation expansion and operation planning models were coupled. Scenarios toward carbon neutrality in a Polish coal-based power system were built. Ignoring technical constraints leads to underestimating system's need for flexibility. Model coupling improves the robustness of elaborated long-term energy scenarios.